ULAMAA’ ON THE POLITICAL STAGE - Syam, Firdaus; Khalill, Munawar (Journal of Social Political Sciences, 2021)
The participation of ulamaa’ in politics was seen as a reference point for determining the vote acquisition that would be obtained by political parties. The recruitment of ulamaa’ before the general election is strong evidence that the role of ulamaa’ in politics was very important, not only in the religious sphere but in the social and political sphere of society. The participation of ulamaa’ gave rise to pro and contra views in the midst of society. The pro view saw ulamaa’ as being able to cleaned up the political atmosphere, while the counter view sees politics as limited to power and tarnishes the ulamaa's image. This study aimed to explained the involvement of ulamaa’ in the Aceh Party and the Aceh Sovereign Party in Aceh Barat Daya, the involvement of ulamaa’ is abled to influenced policies in local parties and saw people's views on the involvement of ulamaa’ in politics. The data required in writing this thesis is obtained through library and field research. Literature research was carried out by reading text books, statutory regulations, and other reading material related to this research, while field research was carried out by interviewing and observing. The results showed that the involvement of ulamaa’ in the Aceh Party and the Aceh Sovereign Party in Aceh Barat Daya was based on the recruitment of the Aceh Party and the Aceh Sovereign Party to the ulamaa’ because they provided many benefits to the party. The desire of the ulamaa’ themselves and getting support from the community was also a factor in the involvement of ulamaa’ in politics. This happened because the ulamaa’ would to changed the existing government system into a better system. The involvement of the ulamaa’ had a big influence on the party, namely being abled to changed policies in the Aceh Party and the Aceh Sovereign Party in Aceh Barat Daya so that it was able to increased the number of votes obtained by the Aceh Party and the Aceh Sovereign Party. Some of the people of Southwest Aceh view the involvement of ulamaa’ in the Aceh Party and the Aceh Sovereign Party as a natural thing, the involvement of the ulama was considered capable of providing a cleaner nuance in politics, while others think that when the ulamaa’ were involved in politics he would only gave priority to himself and abled to damaged his image as a cleric. Involvement of ulamaa’ in politics was expected to be more able to heard and conveyed the aspirations of the people, and to keeped the politics they lived in clean so that their image was maintained so that the public's view of ulamaa’ involvement remains good and supportive.